Effects of mirror therapy vs modified constraint induced movement therapy on upper extremity in subacute stroke patients (Bangladesh Journal of Medical Science, 2021)
Objective: To compare and to examine the effectiveness of mirror therapy and modified constraint induced movement therapy (mCIMT) on upper extremity in subacute stroke patients.Background: Stroke or cerebral vascular accident is sudden dead of the brain cells due to inadequate blood flow. The WHO defines stroke as rapidly developing clinical signs of focal disturbance of cerebral function, with symptoms lasting for 24hrs or longer or leading to death, with no apparent cause other than of vascular origin. The most common consequence of stroke is loss of upper limb function. The protocol planned for improving the function of upper limb are mirror therapy and modified constraint induced movement therapy (mCIMT). Mirror therapy is a simple and inexpensive treatment which uses the visual information activating the premotor and motor cortex of the brain. This is explained by activation of so called mirrorneuron system. Whereas mCIMT utilises the redundant pathway in brain through neuro plasticity.Methodology: A total of 30 participants with subacute stroke were selected. The inclusion criteria are both gender of age 55-70 years and duration of 2-12 months of post stroke. Participants with mini mental state examination score